Advertisement Remove all ads

Simplify : 2{"M"-3("N"+Overline("M"-2"N"))} - Mathematics

Sum

Simplify : `2{"m"-3("n"+overline("m"-2"n"))}`

Advertisement Remove all ads

Solution

`2{"m"-3("n"+overline("m"-2"n"))}`

= 2{m − 3 (n + m − 2n)}

= 2{m − 3 (m − 3 (m − n)}

= 2{m − 3m + 3n}

= 2{3n − 2m}

= 6n − 4m

Concept: Simplification of Expressions
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Selina Concise Mathematics Class 8 ICSE
Chapter 11 Algebraic Expressions
Exercise 11 (E) | Q 1.04 | Page 147
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×